Emotional dependency and social skills in adolescents aged 14 to 16 - Lema Pujota, Joseline Lizbeth; Silva Paredes, Christian Rolando (Revista Universidad de Guayaquil, 2025)
The aim of this research was to identify the relationship between emotional dependency and social skills in adolescents between 14 and 16 years of age in an educational institution. For this purpose, a quantitative approach was adopted, with a non-experimental, descriptive-correlational and cross-sectional design. A sample of 142 adolescents were administered the Couples Emotional Dependence Scale for Adolescents (EDEA), the Goldstein Social Skills Assessment Scale and a sociodemographic survey validated by experts. The results, obtained by means of a linear regression model, yielded a Pearson correlation coefficient of 0.109 and a bilateral significance level of 0.199, which led to the acceptance of the null hypothesis, that is, that there is no correlation between emotional dependency and social skills in adolescents aged 14 to 16 years from an educational institution. It was concluded that this result could be due to other factors not considered in this research, such as the family environment, the socioeconomic context or the personal history of the participants. Further research addressing these factors is recommended to obtain a more complete picture.